The Effectiveness of Four Square Writing Method in Developing Students' Writing Skills in Recount Text for Students of English Language Education - Rina Puji Utami; Henny Roesellaningtias; Caltira Rosiana (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
There are four skills in mastering English to gain good communication in English well in daily life in this globalization era. Writing skills have become one of the most interesting skills that are researched in the English Language Education students. In developing the student's writing skills, the lecturer must have an appropriate method to teach writing. The four Square Writing method is one of the methods that can help students develop their ideas in an organized way and write systematically. This research is about the efficaciousness of the Four Square Writing method in developing students' writing skills in recounting text among the third-semester students of English Language Education at STKIP PGRI Nganjuk in the 2023/2024 academic year. The purpose of the research is to know the efficaciousness of the Four Square Writing Method in increasing students' writing skills in recount text among the third-semester students of English Language Education at STKIP PGRI Nganjuk in the 2023/2024 academic year. The researcher used in this research is the methodology of Pre pre-experimental design (one group pre-test post-test design). The data of the tests were then calculated by using a t-test. It could be seen from the result of the calculation that the student's scores on the post-test are higher than those on the pre-test. The mean score of the post-test was 75,5. Meanwhile, the mean score of the pre-test was 68,16. Furthermore, based on the statistical calculation with the significant level of 5% It means that t0 15,45 is higher than t (1-a) which was 2,06866.